[DC] Learning Tornado Formation via Collaborative Mixed Reality - Chiou, Yan-Ming; Barmaki, Roghayeh (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
With the rise of attention to global warming which brings in more extreme weather and climate conditions, the earth science education would be one of the crucial topics for the next generation. Mixed-Reality has been shown to offer more engaging and effective learning solutions on essential science topics, such as math, physics, and chemistry. However, there are few augmented reality and mixed reality applications on earth science subject. Also, collaborative learning has been shown to be beneficial for student learning by aspiring student curiosity, and the ability of cooperation. In this paper, we propose a Mixed Reality Tornado Simulator which offers an earth science education intervention in a collaborative mixed reality setting. Students and their instructor can wear see-through head-mounted displays to cooperate on learning the knowledge of the formation and its damage cause on human-built structures, farming, and vegetation by using our proposed mixed reality application. Also, for evaluating the learning performance in this mixed reality setting, we will study the students cognitive load using standard survey instruments. We will conduct a controlled study with two conditions to compare the proposed intervention in the head-mounted-display setting, versus a desktop setting to test usability and knowledge gain of the students in those settings.